(untitled) (REMUNOM, 2023)
This study aims to analyze the impact of social media on mental health, addressing the challenges and prospects associated with its use. The adopted methodology is a literature review, involving the analysis of previous studies and relevant publications on the topic. It is expected that the results of this review will provide insights into the positive and negative effects of social media on mental health, as well as identify the key challenges faced by users. Furthermore, it is anticipated that this review will provide a deeper understanding of future perspectives in the field, including possible interventions and strategies to mitigate negative effects and promote a healthy relationship with social media. Based on the analyzed evidence, it is concluded that social media plays a significant role in daily life, affecting mental health in complex ways. Therefore, it is crucial to implement educational, preventive, and awareness measures to promote a healthy and balanced use of social media, ensuring the psychological and emotional well-being of users. Keywords: Social Media; Mental Health; Media.